Built Competitive Advantage Models on Cofee Shop Business in Jakarta - Herminda Herminda; Muhammad Iman Nugroho (Dinasti International Journal of Management Science, 2023)
This research is to determine the influence of entrepreneurial orientation, product innovation, and business location on competitive advantage at coffee shops in Jakarta. This study used quantitative research with a data collection method using a closed model questionnaire technique measured by a likert scale by taking a sample of 200 respondents from 296 coffee shop owners who became the population. Approach modeling and data analysis using the Structure Equetion Model (SEM) using the Lisrel program version 8.8. The resulting structural equation model is KUB = -0.048*OKW + 0.35*INP + 0.53*LOK, with an R square of 0.76 (76%) and nilai Fcount of 5.84 ? 3.84, which means that the three free variables are significant to the varaibel bound it. Thus, the variables of Entrepreneurship Orientation (OKW), Product Innovation (INP) and Business Location (LOK) together affect the competitive advantage (KUB) of coffee shops in Jakarta. The most dominant variable affecting the competitive advantage of coffee shops is the location of the business with a comfortable and safe environment.